2020
DOI: 10.1177/0036850420961610
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior and dynamic damage constitutive model of glass fiber-reinforced Vinyl Ester with different fiber contents

Abstract: Glass fiber-reinforced plastics (GFRP) based on polymer materials are widely used in lightweight impac-resistant structure design. In the process of design and development, it is very important to clarify the mechanical behavior under dynamic load to improve the product performance. Therefore, in this paper, Quasi-stati and dynamic compression behaviors of unidirectional continuous glass fiber-reinforced vinyl ester (GF/VE) composites with five kinds of fiber contents in the fiber direction were measured by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Much literature has recently studied the dynamic behavior of glass fiber-reinforced polymers to improve product performance. Duan et al 41 investigated the quasi-static and dynamic compressive behavior of glass-reinforced vinylester resin using different glass fiber mass fractions. The quasi-static compression tests were conducted using a specific electro-hydraulic servo experimental system.…”
Section: Introductionmentioning
confidence: 99%
“…Much literature has recently studied the dynamic behavior of glass fiber-reinforced polymers to improve product performance. Duan et al 41 investigated the quasi-static and dynamic compressive behavior of glass-reinforced vinylester resin using different glass fiber mass fractions. The quasi-static compression tests were conducted using a specific electro-hydraulic servo experimental system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the proposed dynamic–static conversion equations based on polymers such as plastics and rubbers do not apply to solid propellants. Further, current studies mainly focus on the strength and stiffness of materials, the analytical prediction methods, and the development of constitutive models [ 29 , 30 , 31 ]. However, materials in industrial applications are subjected to not only static but also dynamic loads, probably both at the same time, or both occurring sequentially [ 32 ].…”
Section: Introductionmentioning
confidence: 99%